Characterising signalling components mediating root architecture in Arabidopsis thaliana - Murphy, Evan (2016)
Our planet is growing rapidly in population and with that comes a demand for resources. To address issues in food security, scientists are looking to the underground parts of plants for novel mechanisms that will eventually lead to enhanced crop traits. Scientists are examining the underlying genetic frameworks to identify which genes play key roles in specific developmental processes. In this study we examined the model plant Arabidopsis thaliana as the roots are easily visualised, the genome has been sequenced, and there are many tools broadly available to work with. This thesis has used a multidisciplinary approach to uncover the signalling cascades revolving around the small signalling peptide RALF34, which is significantly involved in primary and lateral root growth. We have demonstrated, in the following chapters that RALF peptides are inherent to normative lateral root initiation, potentially regulated through shoot derived auxin. Furthermore, RALF4 and 34 peptides play a strong role in restricting primary root growth, and that together these peptides have an additive effect on cell elongation. Lastly, we identify several leucine-rich repeat receptor-like proteins, kinase proteins, and cell wall remodelling enzymes, which putatively play unique and diverse roles during primary and lateral root development. Taken together, this thesis provides novel and unique insights into new signalling pathways during root growth, which may in future aid in agronomic enterprises.